A young adult patient with Philadelphia positive acute lymphoblastic leukemia presenting with extreme hyperleukocytosis - Gulten Tikit; Elif Yucesu; Aliye Serpil Sarıfakıoglu; Imdat Dilek; Sule Mine Bakanay (Clinical Case Reports)
Key Clinical Message Extreme hyperleukocytosis (Leukocyte count >200 × 109/L) in an adolescent young adult (AYA) patient with B‐ALL could result in mild symptoms of leukostasis. Hyperleukocytosis requires prompt initiation of therapy with adequate hydration, cytoreduction and prevention of tumor lysis. Ph + B‐ALL may present with extreme hyperleukocytosis and may be resistant to initial pre‐phase therapy. In such cases, leukocytapheresis is beneficial in reducing the leukocyte count as well as controlling the symptoms.